The Leadership Development Interface: Aligning Leaders and Organizations Toward More Effective Leadership Learning - Hanson, Byron (SAGE, 2013)
The Problem Leadership Development research and practice has consistently focused on specific methods and interventions to the degree that our understanding of what good leadership development looks like is much clearer. The problem however, with current thinking on leadership development and the evaluation of leadership development is that we are not exploring the extent to which the individual leader and the organization they work for are connected and aligned. For evaluators of leadership development this exploration is a key aspect in measuring the systemic nature of leadership development and not merely the intervention. How do individual leaders navigate their personal leadership development journey and how do the organizations for which they work interface with them to provide effective development opportunities and practice? The Solution This article makes the case that we need to evaluate and articulate the leadership development process differently; to move away from isolated methods and toward an interconnected process of personal and organizational discovery and learning. When leaders and organizations activate the interconnectedness of leadership development, learning may become more reciprocal and aligned which could drive better development outcomes and value. The Leadership Development Interface Model, developed through research and literature data, provides an interconnected perspective of leadership development and explores a “whole system” view so both leaders and organizations can engage, plan, and evaluate their development effort in an aligned and supported way. The Stakeholders Leaders and their direct managers in organizations, HR and development specialists.